Integrated food safety and nutrition assessments in the dairy cattle value chain in Tanzania - Häsler, Barbara; Msalya, G.; Garza, M.; Fornace, K.; Eltholth, Mahmoud; Kurwijila, Lusato R.; Rushton, Jonathan; Grace, Delia (Elsevier, 2018)
The consumption of even small amounts of animal-source foods has the potential to improve nutrition, especially in vulnerable households. However, scaling up their production bears food safety risks that are often overlooked due to a disconnect between human nutrition and animal sciences. The aim of this scoping study in Tanzania was to identify opportunities for nutritional and food safety benefits from cow milk. Questionnaires were administered to 156 producers and 157 consumers in 10 villages in Lushoto and Mvomero districts. Farmers reported that veterinary medicines such as oxytetracyclines, penicillin and streptomycin were frequently given to cattle, and a majority did not discard milk during or after treatment. Less than half of the producers boiled milk, although sale of fermented milk, made by spontaneous fermentation of raw milk, was common. Cattle management was characterised by low levels of biosecurity, hygienic practices and disease control. A majority of consumers reported not to have enough food to meet their family needs. The Food Consumption Score was acceptable for all households, but significantly higher for households with dairy cattle. When making purchasing decisions, the appearance of milk and trust in the supplier were more important considerations than hygiene practices observed. A total of 26% of consumers reported to consume raw milk “usually” or “sometimes” and 54% of consumers reported to drink fermented milk “usually” or “sometimes”. Consumers had a positive attitude towards milk and concern for quality but most thought there was no risk of illness from milk consumption. The findings promote understanding of the complexity surrounding the local food environment and practices related to the production and consumption of dairy products and allow shaping recommendations for nutrition-sensitive livestock interventions.